2023
DOI: 10.1101/2023.09.27.559820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contact-FP: a dimerization-dependent fluorescent protein toolkit for visualizing membrane contact site dynamics

Gregory E. Miner,
Sidney Y. Smith,
Wendy K. Showalter
et al.

Abstract: Membrane contact sites (MCSs) are sites of close apposition between two organelles used to exchange ions, lipids, and information. Cells respond to changing environmental or developmental conditions by modulating the number, extent, or duration of MCSs. Because of their small size and dynamic nature, tools to study the dynamics of MCSs in live cells have been limited. Dimerization-dependent fluorescent proteins (ddFPs) targeted to organelle membranes are an ideal tool for studying MCS dynamics because they rev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…One possibility is to utilize split Halo tag and recently developed reversible Halo ligands (Ishikawa et al, 2012;Kompa et al, 2023;Minner-Meinen et al, 2021;Shao et al, 2021) to develop orthogonal split FPs that work with splitFAST. Additionally, it is possible to combine FABCON with other ddFP-based tool kits to investigate multiple contact sites (Alford et al, 2012;Miner et al, 2023a). Overall, our work provides a new tool kit for the detection of lipid droplet-organelle contact sites and beyond; we have demonstrated that FABCON is capable of revealing the dynamics of contact sites and generating observation-based hypotheses.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…One possibility is to utilize split Halo tag and recently developed reversible Halo ligands (Ishikawa et al, 2012;Kompa et al, 2023;Minner-Meinen et al, 2021;Shao et al, 2021) to develop orthogonal split FPs that work with splitFAST. Additionally, it is possible to combine FABCON with other ddFP-based tool kits to investigate multiple contact sites (Alford et al, 2012;Miner et al, 2023a). Overall, our work provides a new tool kit for the detection of lipid droplet-organelle contact sites and beyond; we have demonstrated that FABCON is capable of revealing the dynamics of contact sites and generating observation-based hypotheses.…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, determining how these nanoscale subcellular foci are dynamically regulated remains challenging due to the limited spatialtemporal resolution of imaging technologies. During the past decade, proximity-induced reporters, such as split FP (Cieri et al, 2018;Eisenberg-Bord et al, 2016;Harmon et al, 2017;Kakimoto et al, 2018;Shai et al, 2018), dimerized-dependent FP (ddFP) (Alford et al, 2012;Miner et al, 2023a), and fluorescence resonance energy transfer FP pairs (Csordas et al, 2010;Naon et al, 2016;Poteser et al, 2016;Venditti et al, 2019;Wong et al, 2018), have been applied to probe organelle proximity at contact sites. Though these approaches are generalizable and straightforward to apply, the implementation has encountered many roadblocks, including irreversibility, fluorescence leakiness, and low signal-to-noise readout.…”
Section: Discussionmentioning
confidence: 99%